Peer Mentoring and Peer Tutoring Among K–12 Students: A Literature Review. (February 2018) - Goodrich, Andrew
The purpose of this literature review is to examine research on peer mentoring among K–12 students to assist practitioners with how to incorporate these instructional techniques into their own music programs. Primary themes across the music education literature of peer mentoring include the role of music teachers, the role of students as they learn from each other, and the role of socialization. This article concludes with implications for music educators and recommendations for future studies to inform practice and to guide further research into peer mentoring among K–12 students.